Detection, attribution and projection of changes in the extreme temperature range in the Northern Hemisphere - Xiao-Fan Feng; Cheng Qian (Advances in Climate Change Research)
The extreme temperature range (ETR) is the span between the highest and lowest temperature of a given year, and is a manifestation of extreme temperature variability. It is regarded as having significant environmental and societal impacts, but the influences of human activities on changes in the ETR remain unclear. Here we performed a detection and attribution analysis of the changes in the ETR over the land areas of the Northern Hemisphere (NH) for the period 1960–2018, based on the optimal fingerprinting approach. We found that anthropogenic forcing could be detected and separated from natural forcing, and greenhouse gas forcing could be detected and separated from anthropogenic aerosol forcing, in the spatiotemporal pattern of the NH and in the regional average of the high latitudes. It is estimated that anthropogenic forcing (greenhouse gas emissions) contributed to 129% (152%) of the significant decreasing trend in the NH-averaged ETR. Moreover, compared to the average of 1999–2018, the NH (North America)-averaged ETR was projected to further significantly decrease by 6.7 °C (14.0 °C) in 2081–2100 under the SSP5-8.5 scenario, based on attribution-constrained projection, the magnitude of which was larger than in the models’ raw outputs. In contrast, the ETR was projected to increase significantly in the Mediterranean and adjacent regions under the SSP5-8.5 scenario, and in Central Europe, West Africa, Central Asia, South Asia, and parts of China under the SSP1-1.9 scenario. These results have important implications for understanding and predicting the effects of human activities on changes in extreme temperature variability and for adaptation to these changes in the future.